Assessment of the DNA Barcodes Characteristic of Phalaenopsis deliciosa based on matK, rbcL, and ITS - Nada Nisrina Maulidya; Siti Rohimah; Zakiyah Ramadany; Tri Ratnasari; Mukhamad Su'udi (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Indonesia has high biodiversity for plant species, including orchids with medicinal potential such as Phalaenopsis deliciosa. Generally, morphological characters, especially in flowers are used for orchids identification. However, when the plants are not in the flowering period, the identification becomes difficult. Therefore an alternative method, such as molecular identification (DNA barcoding) needs to be applied for the best solution. This research aims to identify and compare three markers (matK, rbcL, ITS) for their function as potential barcodes for Phalaenopsis deliciosa. This study was conducted by DNA amplification using three different markers set. The data were analyzed using Bioedit, BLAST, and ClustalX. The result found that the identity level of matK, rbcL, and ITS to other orchids species was 99-98%, 98%, and 94-96%, respectively. Furthermore, matK and ITS showed high specificity for Phalaenopsis deliciosa, and are therefore recommended as the best molecular identification marker of genus Phalaenopsis.